Surveillance of Patulin in Applesand Commercial Apple Juices Marketed in Chennai,Indiausing HPTLC - Preetika Baskaran, Sarathchandra Ghadevaru (International Journal of Advanced Science and Technology, 2020)
Patulin is amycotoxin (toxic secondary metabolite) produced by several species of fungi and especially Penicilliumexpansum.Extensive studies have proven it to be the most notable contaminant in apple and apple products. The aim of this study was to investigate the patulin concentration in commercial apple juices, apple fruits and fresh juices marketed in Chennai city, India. The survey was conducted on one hundred and twenty apple products comprising of 80 commercial apple juices, 20 apple fruits and 20 fresh juices from retail outlets and vendors in Chennai. The samples were quantitatively estimated using High Performance Liquid Chromatography (HPTLC). Results showed that the overall incidence of patulin contamination was 18% and the concentration ranged between 0 and 38 µg/l. Fresh juices and whole fruits together were detected with a higher incidence (30%) and the concentration ranging from 0 to 18 µg/l compared to commercial apple juices (11%) with concentrations ranging from 0 to 38 µg/l. The low incidence of patulin and the levels within the tolerable limit (< 50 µg/l) recommended by the European Union, indicates the quality of fruit and manufacturing practices followed by the industries.However, the awareness of the apple industry to patulin contamination and the risk posed by its presence needs to be indicated.